The association of the Affordable Care Act with nutrient consumption in adults in the United States - Kirk, Hilary; Tufuor, Theresa A.; Shaver, Amy L.; Nie, Jing; Devarshi, Prasad P.; Marshall, Keri; Mitmesser, Susan Hazels; Noyes, Katia (Frontiers in Public Health, 2023)
The Patient Protection and Affordable Care Act, more commonly known as the ACA, was legislation passed in the United States in 2010 to expand access to health insurance coverage for millions of Americans with a key emphasis on preventive care. Nutrition plays a critical role in overall wellness, disease prevention and resilience to chronic illness but prior to the ACA many Americans did not have adequate health insurance coverage to ensure proper nutrition. With passage of the ACA, more individuals received access to nutritional counseling through their primary care physicians as well as prescription vitamins and supplements free of charge. The objective of this study was to evaluate the impact of a national health insurance reform on nutrient intake among general population, including more vulnerable low-income individuals and patients with chronic conditions. Using data from the National Health and Nutrition Examination Survey (NHANES), we identified 8,443 adults aged 21 years and older who participated in the survey before (2011-2012) and after the ACA (2015-2016) implementation and conducted a subgroup analysis of 952 respondents who identified as Medicaid beneficiaries and 719 patients with a history of cancer. Using pre-post study design and bivariate and multivariable logistic analyses, we compared nutrient intake from food and supplementation before and after the ACA and identified risk factors for inadequate intake. Our results suggest that intake of micronutrients found in nutrient-dense foods, mainly fruit and vegetables, has not changed significantly after the ACA. However, overall use of nutritional supplements increased after the ACA (p=0.05), particularly magnesium (OR=1.02), potassium (OR=0.76), vitamin D (both D2, and D3, OR=1.34), vitamin K (OR=1.15) and zinc (OR= 0.83), for the general population as well as those in our subgroup analysis Cancer Survivors and Medicaid Recipients. Given the association of increased use of nutritional supplements and expansion of insurance access, particularly in our subgroup analysis, more research is necessary to understand the effect of increasing access to nutritional supplements on the overall intake of micro-and macronutrients to meet daily nutritional recommended allowances.